Pengaruh Preferensi Merek, Lifestyle dan Harga terhadap Keputusan Pembelian pada Trend Fashion Thrift di Kalangan Generasi Z di Untag Surabaya - Fanni Nur Erika; Diana Juli Mulyati; Ute Chairuz M. Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The thrift fashion trend is a phenomenon of buying used clothes that are still wearable, either through physical stores, bazaars, or online platforms that are now popular among young people, especially Gen Z. This study uses a quantitative research method with a descriptive research type that aims to analyze the influence of brand preferences, lifestyle, and prices and the interaction of the three on purchasing decisions on the thrift fashion trend among generation Z at UNTAG Surabaya. The population in this study were Generation Z students of the University of 17 August 1945 Surabaya who had made purchases and followed the thrift fashion trend with a slovin sample formula of 100 respondents and determined using a non-probability sampling technique. The data processing technique in this study used SPSS. Data was collected through an e-questionnaire via a google form that included the variables Brand Preference, Lifestyle, Price and Purchase Decision. Based on the results of the partial t-test, it was proven that the Brand Preference variable (X1), Lifestyle (X2), Price variable (X3) had a significant effect on purchasing decisions on the thrift fashion trend among Gen Z at UNTAG Surabaya. Meanwhile, the F test simultaneously shows that Brand Preference (X1), Lifestyle (X2), and Price (X3) simultaneously influence purchasing decisions (Y) on thrift fashion trends among Gen Z at UNTAG Surabaya.